Association between physical activity and general health in teachers of the universities of medical sciences of Fars Province - Sobhanian, S.; Khoshnam, E.; Naderian, M.; Barhagh, HD. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The aim of this study was to examine the association between physical activity and general health in faculty members of the Universities of Medical Sciences of Fars (Iran). The sample of this cross-sectional analytical study was composed of 244 faculty members of the Universities of Medical Sciences of Fars (Iran) in 2018. The data collection instrument included a three-section questionnaire: 1) Demographic characteristics (age, gender, and household income). 2) Short questionnaire for the measurement of habitual physical activity in epidemiological studies. 3) Goldberg General Health Questionnaire. Data analysis was performed using SPSS 16. The results showed that there was no significant statistical relationship between physical activity and general health subscales in the sample studied. Future studies about this topic with larger samples and in other regions are recommended.